2004
DOI: 10.1023/b:brea.0000010700.11092.f4
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Response to Primary Chemotherapy in Breast Cancer using Dynamic Contrast-enhanced Magnetic Resonance Imaging

Abstract: DCE-MRI allows prediction of the effect of neoadjuvant chemotherapy in breast cancer. Although in our study tumor volume reduction after two cycles had the strongest predictive value, DCE-MRI has the potential to provide functional parameters that could be integrated to optimize neoadjuvant chemotherapy strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
141
0
3

Year Published

2007
2007
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 222 publications
(150 citation statements)
references
References 25 publications
6
141
0
3
Order By: Relevance
“…The MRI correlation with histopathological size (r ¼ 0.71) is similar to that found previously with correlations of r ¼ 0.75 (Rosen et al, 2003) and 0.72 (Martincich et al, 2004) reported. Other groups have reported correlations of r ¼ 0.6 (Partridge et al, 2002) and r ¼ 0.982 (Cheung et al, 2003).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The MRI correlation with histopathological size (r ¼ 0.71) is similar to that found previously with correlations of r ¼ 0.75 (Rosen et al, 2003) and 0.72 (Martincich et al, 2004) reported. Other groups have reported correlations of r ¼ 0.6 (Partridge et al, 2002) and r ¼ 0.982 (Cheung et al, 2003).…”
Section: Discussionsupporting
confidence: 89%
“…Several studies have suggested that MRI is a more accurate method of delineating residual tumour following neoadjuvant chemotherapy than clinical, ultrasound or mammographic assessment (Boetes et al, 1995;Abraham et al, 1996;Drew et al, 1999Drew et al, , 2001Fischer et al, 1999;Balu-Maestro et al, 2002;Rieber et al, 2002;Cheung et al, 2003;Rosen et al, 2003;Martincich et al, 2004;Warren et al, 2004). Chemotherapy-induced fibrosis has been shown to impair the evaluation of tumour by conventional radiological methods and physical examination (Cocconi et al, 1984;Segel et al, 1988).…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to previous reports, which found correlation coefficients ranging from 0.70 to 0.98 for MRI (Esserman et al, 1999;Partridge et al, 2002;Rosen et al, 2003;Wasser et al, 2003;Martincich et al, 2004). However, a recent retrospective review of neoadjuvant chemotherapy trials from the MD Anderson Cancer Center also found a poor agreement between tumour size measurements by mammography or ultrasound and histopathology (Chagpar et al, 2006).…”
Section: Discussionmentioning
confidence: 59%
“…The relative change in MRI measured longest tumor diameter had a high sensitivity and specificity for predicting pathologic response, with only one false positive and one false negative result. MRI has been shown to provide an accurate estimation of tumor size in invasive breast cancer compared with pathological tumor size (27,28) Several other studies of response to NAC in breast cancer patients found that early evaluation of MRI derived tumor diameter was the best predictor of response to NAC, (7,13,(29)(30)(31), although the same relationship was not found in (32).…”
Section: Discussionmentioning
confidence: 99%